Democratization and development Focusing on Tacloban Underwriters Multi-Purpose Cooperative (TUCC). - Amlih, Riadin B. (Riadin B. Amlih, 2009)
The existence of cooperatives was seen as an avenue for the economic development and democratic participation of its members in the community. Meanwhile, a Multi-purpose cooperative has long been serving the community in various ways. To further strengthen this claim that cooperatives contribute to democratization and development, I focused my study on one particular multi-purpose cooperative in the Province of Leyte. The Tacloban Underwriters Multi-purpose Cooperative was studied using the following variables: (1) Open and Voluntary Membership, (2) Democratic Control Cooperatives, (3) Member Economic Participation, (4) Autonomy and Independence, (5) Education, Training and Information, (6) Cooperation among Cooperative, and (7) Concern for the Community Membership Participation. Beyond the given variables, the relation of Tacloban Underwriters Multi-purpose Cooperative to national and regional trends in democratization and development was also looked into. After some researches, the results revealed that Tacloban Underwriters Multi-purpose Cooperative indeed contributes to the democratization and development of its members in a moderate way.